PELUANG MENURUT UNCLOS DAN HUKUM POSITIF INDONESIA UNTUK MEMBUKA KEMBALI EKSPOR PASIR LAUT KE SINGAPURA - Tommy Hendra Purwaka (Jurnal Dinamika Hukum, 2014)
Development of Riau Island Province as one of Indonesian strategic border regions is a must. National and provincial budget used for strengthening the region should obtain finacial support from seasand export revenue. Seasand export revenue, however, could not be expected for the export was banned by the government since 2002. Result of legal research on this matter shows that UNCLOS and Indonesian positive laws give an opportunity to reopen the export. Efforts to reopen the export should be supported by argumentation based on the law of the sea which will be discussed through this paper. Keywords: seasand export, UNCLOS